Phonon symmetries in hexagonal boron nitride probed by incoherent light emission. (9th November 2016) - Vuong, T Q P; Cassabois, G; Valvin, P; Jacques, V; Lee, A Van Der; Zobelli, A; Watanabe, K; Taniguchi, T; Gil, B
Abstract: Layered compounds are stacks of weakly bound two-dimensional atomic crystals, with a prototypal hexagonal structure in graphene, transition metal dichalcogenides and boron nitride. This crystalline anisotropy results in vibrational modes with specific symmetries depending on the in-plane or out-of-plane atomic displacements. We show that polarization-resolved photoluminescence measurements in hexagonal boron nitride reflect the phonon symmetries in this layered semiconductor. Experiments performed with a detection on the sample edge, perpendicular to the c -axis, reveal the strong polarization-dependence of the emission lines corresponding to the recombination assisted by the three acoustic phonon modes. We elucidate the dipole orientation of the fundamental indirect exciton. We demonstrate evidence of the so-far missing phonon replica due to the optical out-of-plane phonon mode.